Investigating the Relation Between Heavy Precipitation and Circulation Patterns of the Upper Atmosphere (case study : Southern Khorasan Province) - Hasan Ali Gayoor; Amir Hossain Halabian; Bijan Saberi; Fereshteh Hossain Ali Poorjazi (مخاطرات محیط طبیعی, 2013)
For exact recognition of heavy precipitation of a region there is a need to sufficient studies about dynamic and synoptic conditions of that occurrence. In this study we used environmental-to-circulation method and approach and data from 61 stations of meteorology organizations and 9 hydrometric stations of South Khorasan province. In relation to the circulation patterns of the upper atmosphere by using base component analysis and cluster analysis between 1990-2007, 4 circulation patterns were identified. In analysis of these precipitations one representative day was introduced for every circulation pattern. The results of data analysis showed that the circulation patterns N0.2 and 4 justify the most of precipitations and more than 60% of these precipitations occur in these two patterns. In the point of view of the origin of humidity source we can say that 3 regions have had roles in these precipitations: Mediterranean Sea, the Arabian Sea, and the Persian Gulf. These findings can play an important role in forecasting the precipitation and preventing from flooding in the region.